2017
DOI: 10.3390/ijerph14060627
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in Drinking Water and Incidence of Suicide: A Nationwide Individual-Level Cohort Study with 22 Years of Follow-Up

Abstract: Suicide is a major public health concern. High-dose lithium is used to stabilize mood and prevent suicide in patients with affective disorders. Lithium occurs naturally in drinking water worldwide in much lower doses, but with large geographical variation. Several studies conducted at an aggregate level have suggested an association between lithium in drinking water and a reduced risk of suicide; however, a causal relation is uncertain. Individual-level register-based data on the entire Danish adult population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 42 publications
0
66
2
Order By: Relevance
“…Despite [55,68]. Knudsen et al [63] found no association of exposure to lithium in drinking water in Denmark and risk of suicide in bipolar disorder.…”
Section: Other Treatments: Antidepressantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite [55,68]. Knudsen et al [63] found no association of exposure to lithium in drinking water in Denmark and risk of suicide in bipolar disorder.…”
Section: Other Treatments: Antidepressantsmentioning
confidence: 99%
“…Finally, for lithium, we carried out a systematic search and summarized findings of a growing number of studies that evaluated associations of the low concentrations of lithium in local drinking water with reported suicide or homicide rates in the same communities or regions. We found 18 such reports [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Several of these reports involved an apparently single set of data from Austria, and their findings are pooled [57][58][59]62].…”
Section: Lithium In Drinking Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Li is a naturally occurring element in surface waters, mainly in its ionic form [ 54 ]. Its concentrations, depending primarily on the processes of weathering of mineral rocks [ 19 , 55 ], differ depending on geographical region [ 23 , 56 ] and are clearly correlated with its natural resources in a certain region [ 10 ]. The available literature does not provide data on the variability of Li concentrations in water depending on time; however, taking into account its chemical properties in aqueous solutions, it can be considered as a relatively constant value.…”
Section: Water As a Source Of Lithiummentioning
confidence: 99%
“…Concentrations reaching approximately 200 μg/L were found in drinking water in selected regions of the USA (Texas), Greece, Japan, England, and Italy [ 63 65 ]. In comparison with the medicinal doses of 600–2400 mg Li 2 CO 3 /day (113–452 mg Li/day), concentrations occurring in surface and underground waters are very low [ 55 , 66 , 67 ]. Even though the concentrations of Li in some regions of the world reach as much as 5.2 mg/L [ 68 ], in tap water in Europe, they generally reach several dozen micrograms per liter [ 13 , 68 ].…”
Section: Water As a Source Of Lithiummentioning
confidence: 99%